Ultrasound‐guided retrobulbar nerve block in horses: a cadaveric study. (11th October 2012) - Morath, Ute; Luyet, Cédric; Spadavecchia, Claudia; Stoffel, Michael H; Hatch, Garry M
Abstract: Objective To develop an ultrasound‐guided technique for retrobulbar nerve block in horses, and to compare the distribution of three different volumes of injected contrast medium (CM) (4, 8 and 12 mL), with the hypothesis that successful placement of the needle within the retractor bulbi muscle cone would lead to the most effective dispersal of CM towards the nerves leaving the orbital fissure. Study design Prospective experimental cadaver study. Animals Twenty equine cadavers. Methods Ultrasound‐guided retrobulbar injections were performed in 40 cadaver orbits. Ultrasound visualization of needle placement within the retractor bulbi muscle cone and spread of injected CM towards the orbital fissure were scored. Needle position and destination of CM were then assessed using computerized tomography (CT), and comparisons performed between ultrasonographic visualization of orbital structures and success rate of injections (intraconal needle placement, CM reaching the orbital fissure). Results Higher scores for ultrasound visualization resulted in a higher success rate for intraconal CM injection, as documented on the CT images. Successful intraconal placement of the needle (22/34 orbits) resulted in CM always reaching the orbital fissure. CM also reached the orbital fissure in six orbits where needle placement was extraconal. With 4, 8 and 12 mL CM, the orbital fissure was reached in 16/34, 23/34 and 28/34 injections, respectively. Conclusion and clinical relevance The present study demonstrates the use of ultrasound for visualization of anatomical structures and needle placement during retrobulbar injections in equine orbits. However, this approach needs to be repeated in controlled clinical trials to assess practicability and effectiveness in clinical practice.